جودة البرامج الهندسية والاعتمادية (تجربة اعتماد برنامج الهندسة المدنية / جامعة بغداد ) - محمود, اوس حاتم (Journal of Economics and Administrative Sciences, 2010)
Promotion the level of academic education is a part of reform and renewal process in the contemporary communities. Investment in education and scientific research is an investment is in the future, and it is the point of right start to construct a progressive community that able to face challenges, overcome problems and achieve comprehensive development goals. Good education, in the comprehensive meaning, is that which fulfills quality conditions in every aspect, response to labor market requirements and fit for rapidly variables of science fields with all their sections and divisions. Development requirements and labor market needs obliged to an engineer of high scientific quality and vocational skills، which oblige the educational institutions to create a complete system to guaranty quality in it. Subjection technical educational program to accreditation process according to organize and methodical scientific and unified form within the frame of specific standers by local, Arabian and international independent bodies, which guaranty goodness and make strong incentive for the continual improvement, on the condition that accreditation process, with self – evaluation، should be done by the organization it self. The researcher will focus on the goodness guaranty activity in high education via accreditation process and present the importance of some institutions and international accreditation boards and standers they adapted to value educational institutions and propose standers fit to Iraqi environment to be adopted during self – evaluation of the civil engineering department\ Baghdad university to gain accreditation board for engineering and technology.